2020
DOI: 10.12775/jehs.2020.10.03.020
|View full text |Cite
|
Sign up to set email alerts
|

Features of the HRV, endocrine and metabolic parameters in persons whose immune status is susceptible or resistant to chronic stress

Abstract: Background.In the previous studies, we compared the individuals who were almost identical to the average value of LF/HF ratio and its dispersion, but with opposite deviations from the norm of immunity. Two profiles of EEG have been created that reflect the differences between the two clusters. The first profile contains the parameters that in stress-sensitive individuals are in the zone of narrowed norm, whereas in stress-resistant individuals they are to some degree elevated, or at least exceed those in stres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…The calculation of the Entropy of the peripheral blood Immunocytogram, as well as the Splenocytogram and Thymocytogram of smear prints in rats was first used by IL Popovych in 2007 [38], using the idea of OG Yushkovs'ka [51] to use the calculation of the Entropy of Leukocytogram of peripheral blood in athletes for estimation their adaptive responses. The creativity of this approach is demonstrated in subsequent studies by IL Popovych et al [10,14,16,[21][22][23]25,29,30,39,40,[43][44][45][46][47]49,50,[52][53][54] and other representatives of the Truskavetsian Scientific School [11,12,20,37]. However, Entropy was not the focus of the analysis it occupied in this study.…”
Section: Results and Discusionmentioning
confidence: 80%
“…The calculation of the Entropy of the peripheral blood Immunocytogram, as well as the Splenocytogram and Thymocytogram of smear prints in rats was first used by IL Popovych in 2007 [38], using the idea of OG Yushkovs'ka [51] to use the calculation of the Entropy of Leukocytogram of peripheral blood in athletes for estimation their adaptive responses. The creativity of this approach is demonstrated in subsequent studies by IL Popovych et al [10,14,16,[21][22][23]25,29,30,39,40,[43][44][45][46][47]49,50,[52][53][54] and other representatives of the Truskavetsian Scientific School [11,12,20,37]. However, Entropy was not the focus of the analysis it occupied in this study.…”
Section: Results and Discusionmentioning
confidence: 80%
“…The experiment was completed by decapitation of rats in order to collect as much blood as possible. The plasma levels of the hormones of adaptation were determined: corticosterone, triiodothyronine and testosterone (by the ELISA [12]); as well as parameters of lipids peroxidation: diene conjugates (spectrophotometry of the heptane phase of the lipids extract [4]) and malonic dyaldehid (in the test with thiobarbituric acid [1]), antioxidant enzymes: superoxide dismutase erythrocytes (according to the degree of inhibition of reduction of nitroblue tetrazolium in the presence of N-methylphenazonium metasulphate and NADH [3,20]) and catalase plasma (at the rate of decomposition of hydrogen peroxide [13]). Electrolytes: calcium (by reaction with arsenase III), phosphates (phosphate-molybdate method), sodium and potassium (flamming photometry) were determined in plasma and daily urine.…”
Section: Methodsmentioning
confidence: 99%
“…The question of mediators of the immunomodulatory action of urea and creatinine remains open. Standing on the positions of the concepts of functional-metabolic continuum [6] and neuroendocrine immunomodulation [11,[18][19][20]22,24,[26][27][28][30][31][32] we hypothesized the mediating role of mediators of the autonomic nervous system and adaptive hormones. In an experiment on rats, we showed that the modulating effects of nitrogenous metabolites on neuroendocrine parameters are quite pronounced and almost identical in terms of bilirubin (R=0,603), creatinine (R=0,602), uric acid (R=0,599) and urea (R=0,586).…”
Section: Introductionmentioning
confidence: 99%
“…However, at Truskavets' spa water monotherapy is a rare exception for specific contingents, whereas the vast majority of patients use a balneotherapy complex: drinking of Naftussya, application of ozokerite and mineral baths [20]. The immune responses to ozokerite in partial [8,9,20,22] and balneotherapeutic complex in general [13,14,25] are also ambiguous which is a separate manifestation of the multivariate effects on the body of balneological agents as adaptogens as well as stressors [2,4,6,7,16,17,24]. Therefore, the purpose of this study is to analyze variants of immune responses to balneofactors of Truskavets' spa.…”
Section: Introductionmentioning
confidence: 99%